2022
DOI: 10.1186/s12954-022-00702-9
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to opioid agonist therapy predicts uptake of direct-acting antivirals in people who use drugs: results from the French national healthcare database (the ANRS FANTASIO study)

Abstract: Background Opioid agonist therapy (OAT) is associated with reduced injection, reduced HCV transmission, and more opportunities to initiate hepatitis C virus (HCV) treatment in people who use drugs (PWUD). We aimed to study the extent to which adherence to OAT was predictive of increased uptake of direct-acting antivirals (DAA) in PWUD with chronic HCV infection. Methods Using the French national healthcare system database, we targeted PWUD (i.e. wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Furthermore, this result suggests that the decrease in HCV-related mortality-and therefore in infectious disease-related mortality overall-among PHID could be strengthened by adequately scaling up DAA [11,22,23]. Currently, too many barriers exist [24][25][26] to this scaleup, yet hope lies in innovative multilevel interventions and outreach strategies that have proven efficient in reaching and engaging PHID in HCV testing and prevention [27][28][29][30][31]. It has been shown that multidisciplinary, people-centred strategies improves HCV linkage to care and adherence to treatment in a variety of settings [32].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this result suggests that the decrease in HCV-related mortality-and therefore in infectious disease-related mortality overall-among PHID could be strengthened by adequately scaling up DAA [11,22,23]. Currently, too many barriers exist [24][25][26] to this scaleup, yet hope lies in innovative multilevel interventions and outreach strategies that have proven efficient in reaching and engaging PHID in HCV testing and prevention [27][28][29][30][31]. It has been shown that multidisciplinary, people-centred strategies improves HCV linkage to care and adherence to treatment in a variety of settings [32].…”
Section: Discussionmentioning
confidence: 99%